Digital Transformation in SMEs in West Java Digital Marketing Capability Analysis and Use of Chatbots in CRM - S.Manggabarani, Alfatih; Hadi, Prasetyo; Marzuki, Faisal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This research examines the impact of Digital Marketing Capabilities on Marketing Performance, mediated by the use of CRM Chatbots in SMEs in West Java. Utilizing SmartPLS 3.2.9 software for analysis, the study finds that Digital Marketing Capabilities significantly influence Marketing Performance both directly and through CRM Chatbots. These results underscore the importance of robust Digital Marketing Capabilities and CRM Chatbot usage in enhancing the Marketing Performance of SMEs. The findings contribute valuable insights into the factors affecting marketing outcomes and highlight the need for strategic management of Digital Marketing and Media Capabilities to support digital transformation in the market.